Helping Young People Stay Afloat: A Qualitative Study of Community Resources and Supports for LGBTQ Adolescents in the United States and Canada. Issue 8 (3rd July 2018) - Eisenberg, Marla E.; Mehus, Christopher J.; Saewyc, Elizabeth M.; Corliss, Heather L.; Gower, Amy L.; Sullivan, Richard; Porta, Carolyn M.
ABSTRACT: LGBTQ youth are at increased risk of poor health outcomes. This qualitative study gathered data from LGBTQ adolescents regarding their communities and describes the resources they draw on for support. We conducted 66 go-along interviews with diverse LGBTQ adolescents (mean age = 16.6) in Minnesota, Massachusetts, and British Columbia in 2014–2015, in which interviewers accompanied participants in their communities to better understand those contexts. Their responses were systematically organized and coded for common themes, reflecting levels of the social ecological model. Participants described resources at each level, emphasizing organizational, community, and social factors such as LGBTQ youth organizations and events, media presence, and visibility of LGBTQ adults. Numerous resources were identified, and representative themes were highly consistent across locations, genders, orientations, racial/ethnic groups, and city size. Findings suggest new avenues for research with LGBTQ youth and many opportunities for communities to create and expand resources and supports for this population.